Kajian Sifat Fisikokimia dan Organoleptik Beras Singkong (Manihot Esculenta Crantz) Dengan Modifikasi Secara Pemanasan - Ardiansyah Ardiansyah; Endang Sri Wahyuni (Politeknik Negeri Lampung., 2019)
This study aims to determine the effect of heating on physicochemical properties of cassava flour by modifying the heating and organoleptic of cassava rice with cassava flour modified heating. The experimental design used in this study was a completely randomized design, consisting of one factor with six levels of treatment namely 0 minutes warm-up time, 15 minutes, 30 minutes, 45 minutes 60 minutes and 75 minutes. The results of the study data were analyzed by anova test and carried out by the Tukey HSD test. From the results of the study it was concluded that there was a warming effect on digestibility, cassava starch resistant starch modified heating. Cassava rice with cassava flour modified heating is not liked by panelists.